Nanoexposure, Unusual Diseases, and New Health and Safety Concerns - Yuguo Song; Shichuan Tang (The Scientific World Journal)
Accumulating studies in animals have shown that nanoparticles could cause unusual rapid lung injury and extrapulmonary toxicity. Whether exposure of workers to nanoparticles may result in some unexpected damage as seen in animals is still a big concern. We previously reported findings regarding a group of patients exposed to nanoparticles and presenting with an unusual disease. The reported disease was characterized by bilateral chest fluid, pulmonary fibrosis, pleural granuloma, and multiorgan damage and was highly associated with the nanoparticle exposure. To strengthen this association, further information on exposure and the disease was collected and discussed. Our studies show that some kinds of nanomaterials, such as silica nanoparticles and nanosilicates, may be very toxic and even fatal to occupational workers exposed to them without any effective personal protective equipment. More research and collaborative efforts on nanosafety are required in order to prevent and minimize the potential hazards of nanomaterials to humans and the environment.